Implementasi Program Studepreneur Sebagai Upaya Menciptakan Wirausaha Baru dan Model Pengembangan Kewirausahaan Perguruan Tinggi - Dito Rinaldo; Mirza Hedismarlina Yuneline; Ivan Diryana (Jurnal Pengabdian Pada Masyarakat, 2017)
IMPLEMENTATION OF STUDEPRENEUR PROGRAM AS AN EFFORTS IN CREATING NEW ENTREPRENEURS AND THE ENTREPRENEURSHIP DEVELOPMENT MODEL FOR HIGHER EDUCATION. This Community Service Program is related to the implementation of the Studepreneur program, which is a business incubator program in STIE Ekuitas. Studepreneur program is available to strengthen the business that run by students, either obtained from STIE Ekuitas and outside its. The Studepreneur program is implemented within 1 (one) year. In the implementation of the program, STIE Ekuitas team of community service program collaborate with various parties such as Kadin, financial institutions, BPOM and other parties. The Parties involved directly in the implementation of 7 (seven) levels of Studepreneur, either as trainer, consultant, resource person or assistant. The STIE Ekuitas team creates a model of entrepreneurship development, which is expected to be a reference in the entrepreneurship development program at STIE Ekuitas and other universities. The entrepreneurship development model of STIE Ekuitas is based on the experience and evaluation results of the Studepreneur program period 2016-2017, and will be implemented in the entrepreneurship development program in period 2017-2018. In addition this community service program create 13 new entrepreneurs.